DRC Health Financing Reform for UHC : Part 2. Mobilization and Allocation of Resources for Health - World Bank (World Bank, Washington, DC, 2021)
Several studies have identified problems in the DRC health sector, including: low budget allocation, high household expenditure, dependence on external funding, poor use of available resources, low budget execution, governance problems and a decentralization process that remains largely theoretical. The first part of this analysis, a fiscal space analysis (FSA) report provided a new and updated overview of the health sector in relation to the government’s new priorities in the reframed 2019-2022 National Health Development Plan (NHDP). This second report focuses on revenue distribution between the central and provincial levels of the health system and on ways to improve resource mobilization. The report notes that decentralization is a new and developing system in the DRC, politically, technically and financially.